SLC11A1 (NRAMP1) polymorphisms and tuberculosis susceptibility: updated systematic review and meta-analysis. - XiangWei Li; Yu Yang; Feng Zhou; Yunzhi Zhang; Hongzhou Lu; Qi Jin; Lei Gao (PLoS ONE, 2011)
Background Natural resistance associated macrophage protein 1 (NRAMP1), encoded by the SLC11A1 gene, has been described to regulate macrophage activation and be associated with infectious and autoimmune diseases. The relation between SLC11A1 polymorphisms and tuberculosis susceptibility has been studied in different populations. Methods We systematically reviewed published studies on SLC11A1 polymorphisms and tuberculosis susceptibility until September 15, 2010 and quantitatively summarized associations of the most widely studied polymorphisms using meta-analysis. Results In total, 36 eligible articles were included in this review. In Meta-analysis, significant associations were observed between tuberculosis risk and widely studied SLC11A1 polymorphisms with summarized odds ratio of 1.35 (95%CI, 1.17-1.54), 1.25 (95% CI, 1.04-1.50), 1.23 (95% CI, 1.04-1.44), 1.31 (95%CI, 1.08-1.59) for 3' UTR, D543N, INT4, and 5' (GT)n, respectively. Heterogeneity between studies was not pronounced, and the associations did not remarkably vary in the stratified analysis with respect to study population and study base. Conclusions The association between SLC11A1 polymorphisms and tuberculosis susceptibility observed in our analyses supports the hypothesis that NRAMP1 might play an important role in the host defense to the development of tuberculosis.